Associations between Testing and Game Performance in Ice Hockey: A Scoping Review - Vincent Huard Pelletier; Julien Glaude-Roy; André-Philipe Daigle; Jean-François Brunelle; Antoine Bissonnette; Jean Lemoyne (MDPI AG, 2021)
Background: Despite the exhaustive body of literature on the demands of ice hockey, less is known about the relationships between functional performance testing protocols (on ice and off ice) and performance in a game situation. The objective of this review is to provide an overview of these associations. Methods: This review aims to identify on- and off-ice testing currently used in the scientific literature and their possible transfer to game performance as well as identifying research gaps in this field. Results: The 17 selected studies showed that off-ice and on-ice fitness test results can be modestly transferred to the player's selection as well as global and advanced performance indicators. Conclusion: This review of the literature reinforces the importance of strength and conditioning coaches administering previously validated fitness tests. Regarding the academic research, it is also proposed to use performance markers that are directly related to the players' on-ice performance to represent more accurately the relationship between the players' fitness level and their work output. Three research gaps were also identified in relation to targeted populations, choice of performance markers and data measurement methods.